Rh-Catalyzed oxidative C–H activation/annulation: converting anilines to indoles using molecular oxygen as the sole oxidant - Zhang, Guoying; Yu, Hui; Qin, Guiping; Huang, Hanmin (Chemical communications (Cambridge, England), 2014)
A practical and efficient Rh( iii )-catalyzed aerobic C–H activation has been developed for the facile synthesis of a broad range of indoles from simple anilines and alkynes. The protocol could be conducted under mild conditions and used environmentally friendly oxygen as the sole clear oxidant.